(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to investigate factors associated with the quality of life (QoL) of ovarian cancer patients after chemotherapy at the Internal Medicine Department 6, K Hospital in 2024. Subjects and Methods: A prospective descriptive study was conducted on 120 ovarian cancer patients undergoing chemotherapy at Internal Medicine Department 6, K Hospital from March 2024 to December 2024. QoL was assessed using the EORTC QLQ-C30 questionnaire at three time points: before treatment, after three chemotherapy cycles, and upon completion of treatment. Results: A total of 120 patients participated, with a mean age of 52.7 ± 8.5 years. The overall QoL score before treatment was 55.4 ± 12.3, improving to 63.1 ± 9.8 after three chemotherapy cycles, but slightly decreasing to 60.5 ± 10.2 at the end of treatment. Fatigue, nausea, pain, and insomnia were the most common symptoms affecting QoL. The physical function score started at 52.4 ± 11.2, increased to 61.7 ± 10.9 after three cycles, and slightly declined to 59.2 ± 11.0 at the end of treatment. Similar trends were observed in emotional and social function scores. Marital status and educational level showed a significant correlation with QoL scores (p < 0.05). Conclusion: The study provides important insights into improving comprehensive care and support to enhance the quality of life for ovarian cancer patients after chemotherapy.